Drought adaptation and resilience in developing countries - Michael Brüntrup; Daniel Tsegai (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Drought is one of the most damaging natural hazards. Various studies rank it first among all natural hazards by seriousness of impacts such as the loss of life and livelihoods, economic losses and the adverse social and ecosystem effects. In many instances, drought can be a major factor in local conflicts, as well as internal and international migration – these negative effects of drought often persist long after the precipitation returns to normal levels. The causes of droughts are essentially natural, but climate change increases the drought severity, frequency, duration, and spatial extent. The impacts of droughts are also strongly exacerbated by anthropological activities, such as deforestation, overgrazing, soil degradation, and water mismanagement. In turn, the consequences of these activities are also exacerbated by drought, which creates a vicious cycle of ecological degradation and human misery. A reactive approach to droughts is still prevalent in many countries, even though emergency funding is costly, less effective and does not address the long-term causes of vulnerability and lack of sustainability. There is an urgent need to move forward with a paradigm shift from “crisis” to “risk” management, adopting a proactive approach based on the principles of risk reduction and prevention. There is a whole set of effective measures that need to be implemented to increase resilience to drought and minimise its effects. Monitoring and early warning systems along with assessments of the hot spots of vulnerable populations and regions, as well as investments in risk-mitigating measures are the first line of defence. These actions need to become an integral part of national drought policies. Moreover, the full cyclical phenomenon of droughts should be at the core of the drought management plans to take full advantage of the drought preparedness measures. All “drought-relevant” sectors including agriculture, food security, the environment, meteorology, water, energy and tourism have to be included in the drought policy development process and preparedness plans. Integrated proactive drought policies should encapsulate the following aspects: · A strong and comprehensive institution is essential to enhance information-sharing, coordination, cooperation and knowledge-management among various levels of governments, sectors and society. · Drought risk management must be incorporated into both long-term development measures and humanitarian responses. · A combination of top-down (overall drought policy, institutional set-up, funding, modern knowledge) approaches supported by bottom-up (traditional knowledge, local production, livelihoods and decision systems) measures is needed to guarantee the maximum efficiency of implemented measures. · Drought early warning needs to be followed by early action based on reliability, transparency and trust. · Flexibility of funding (contingency planning) must become an integral part of development budget planning. · Drought policy implementation requires capacity-building at the local level to ensure effective interaction between concerned parties. By implementing these approaches, we can use drought as a “connector” that strengthens collaboration among many sectors, levels and actors.
Keywords: 330; Armut und Ungleichheit; Klimawandel